Multiprofessional perspectives on the identification of latent safety threats via in situ simulation: a prospective cohort pilot study. (23rd September 2020) - Rusiecki, Daniel; Walker, Melanie; Douglas, Stuart L; Hoffe, Sharleen; Chaplin, Timothy
Abstract : Objectives: To describe the association between participant profession and the number and type of latent safety threats (LSTs) identified during in situ simulation (ISS). Secondary objectives were to describe the association between both (a) participants' years of experience and LST identification and (b) type of scenario and number of identified LSTs. Methods: Emergency staff physicians (MDs), registered nurses (RNs) and respiratory therapists (RTs) participated in ISS sessions in the emergency department (ED) of a tertiary care teaching hospital. Adult and paediatric scenarios were designed to be high-acuity, low-occurrence resuscitation cases. Simulations were 10 min in duration. A written survey was administered to participants immediately postsimulation, collecting demographic data and perceived LSTs. Survey data was collated and LSTs were grouped using a previously described framework. Results: Thirteen simulation sessions were completed from July to November 2018, with 59 participants (12 MDs, 41 RNs, 6 RTs). Twenty-four unique LSTs were identified from survey data. RNs identified a median of 2 (IQR 1, 2.5) LSTs, significantly more than RTs (0.5 (IQR 0, 1.25), p=0.04). Within respective professions, MDs and RTs most commonly identified equipment issues, and RNs most commonly identified medication issues. Participants with ≤10 years of experience identified a median of 2 (IQR 1, 3) LSTs versus 1 (IQR 1, 2) LST in those with >10 years of experience (p=0.06). Adult and paediatric patient scenarios were associated with the identification of a median of 4 (IQR 3.0, 4.0) and 5 LSTs (IQR 3.5, 6.5), respectively (p=0.15). Conclusions: Inclusion of a multidisciplinary team is important during ISS in order to gain a breadth of perspectives for the identification of LSTs. In our study, participants with ≤10 years of experience and simulations with paediatric scenarios were associated with a higher number of identified LSTs; however, the difference was not statistically significant.